PERANCANGAN GAME EDUKASI HOUSE BUILDER - William Surya Putra; Helmy Thendean (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The House Builder Educational Game is an Educational Game with house constrcution and simulation genre which focuses on the process of building a house. The purpose of the Design is to build a house building educational game that can give elementry school age children the experience and knowledge of house building process. The house building process in this game consists of four main processes which are foundation building, strcuture building, roof building, and house finishing.The foundation building process consists of foundation material arrangement, cement mixture creation, foundation filling, and wall rail installation. House structure building process consists of wall building, door and window installation, and house stairs building. Roof building process consists of  truss creation, roof frame installation, and roof covering. House finishing process consists of floor tile installation and house painting.